CRITICAL DISCOURSE ANALYSIS ON ONLINE NEWS TEXT OF PUBLIC FIGURES DURING COVID-19 PANDEMIC IN INDONESIA - Rafii, Muhammad (LPPM Universitas Pahlawan Tuanku Tambusai, 2024)
This study set out to describe the format of news articles regarding prominent celebrities that hosted big crowds of their fans during the COVID-19 pandemic on detiknews.com and anteraceh.com. Using a qualitative research method was the approach taken in this study. Detik and Anteroaceh, which were both online, were used to gather the data. The news article's headline read: “Jejak Kasus Picu Kerumunan Selebgram Herlin Kenza hingga Jadi Tersangka”, “Kerumunan saat selebgram ini tiba di Lhokseumawe langgar PPKM, Satgas Covid ; kami tidak tau”, and “Selebgram Herlin Kenza divonis bersalah kasus kerumunan, Jaksa : Tak bayar denda, penjara 2 bulan” This study looked at the events that made Herlin Kenza a well-known public figure and led to large gatherings of people during the Corona virus outbreak. The three-dimensional structures text in CDA established by Teun A. van Dijk method, which comprises of micro structure, macro structure, and super structure, was used in the current study.. The results demonstrated that the first and second news of the public figure